2021
DOI: 10.3390/polym13183154
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Properties of PNIPAm-Based Hydrogel Scaffolds for Cartilage Tissue Engineering

Abstract: Poly(N-isopropylacrylamide) (PNIPAm) is a three-dimensional (3D) crosslinked polymer that can interact with human cells and play an important role in the development of tissue morphogenesis in both in vitro and in vivo conditions. PNIPAm-based scaffolds possess many desirable structural and physical properties required for tissue regeneration, but insufficient mechanical strength, biocompatibility, and biomimicry for tissue development remain obstacles for their application in tissue engineering. The structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 169 publications
0
10
0
Order By: Relevance
“…The presence of granular and island-like structures formed during MAPLE deposition can be explained based on both MAPLE behavioral deposition and the polar nature of the solvent aspects. It was previously shown that the phase transition’s dependence on the solvent nature (polar or non-polar) and the hydrogen-bond interactions influence the physico–chemical properties, especially morphology [ 28 ]. When the material reaches the substrate during evaporation, it initially adheres to its surface as random nano-granular clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of granular and island-like structures formed during MAPLE deposition can be explained based on both MAPLE behavioral deposition and the polar nature of the solvent aspects. It was previously shown that the phase transition’s dependence on the solvent nature (polar or non-polar) and the hydrogen-bond interactions influence the physico–chemical properties, especially morphology [ 28 ]. When the material reaches the substrate during evaporation, it initially adheres to its surface as random nano-granular clusters.…”
Section: Resultsmentioning
confidence: 99%
“…As a thermal-responsive polymer that undergoes gelation at around physiological temperature, PNIPAM hydrogel scaffolds have also received considerable attention. Their mechanical and physiochemical properties can be modified by optimising the synthesis parameters and crosslinking approaches to fit the applications of cartilage regeneration and tissue engineered scaffolds [ 95 ].…”
Section: Types Of Hydrogelsmentioning
confidence: 99%
“…Tissue regeneration using advanced scaffolds, growth factors and nutrients, and progenitor or stem cells, provides an alternative treatment option for effectively recreating native cartilage. Hydrogel is the most widely studied and applied material to be scaffolded in the field of cartilage repair and there are two approaches to regenerate cartilage onto scaffolds, namely two-dimensional (2D) and 3D scaffolds [ 18 ], and the application of hydrogels coupled with three-dimensional (3D) printing technologies represents a modern concept in scaffold development in CTE.…”
Section: Introductionmentioning
confidence: 99%